Os significados da relação aluno-personal trainer : aspectos para uma relação duradoura - Ribeiro, José Roberto (2020)
Nowadays, there is a great appreciation of health care, the body and the physical form, subjects that are recurrent themes in the media. Professions that deal with body changes, such as plastic surgeons, physical educators and nutritionists, are highlighted. There is also a growing demand for gyms and bodybuilding, leading to the expansion of this sector, which today has expressive numbers in terms of revenue and in the number of students. This dissertation investigates the relationship developed between the personal trainer and the student (client), identifying which aspects are valued and positively impact the student's loyalty to this service. This is an exploratory research with a qualitative method and application of semi-structured individual interviews with 13 male bodybuilders who have been users of personal trainers’ services for more than three years. It has been concluded that loyalty between the interviewees and their current personal trainer established by a set of aspects, but two of them are fundamental: the achievement, at least partially, of the student's goals with the training program and the existence of some degree of personal affinity between the student and the professional. Also, the confidence in the technical and professional skills of the professional, the motivation transmitted to the student and the flexibility in terms of replacing classes on alternative days or times are very relevant.